Towards a Coupled Regulation and Flexible Ramp Product Marginal Pricing - Chavez-Orostica, H; Lismayes-Aguilar, A (Institute of Electrical and Electronics Engineers Inc., 2020)
Several countries have achieved significant penetration levels of non-dispatchable generation. This integration has led to the necessity of more efficient formulations for frequency regulation ancillary services from an increasing number of technologies. One aspect that has captured particular attention is ramping capability requirements, which have increased for both frequency regulation and intra-dispatch generation ramping. In general, ramping capability requirements for frequency reserves are formulated separately from those associated with intra-dispatch movements; however, during actual operation, reserve and energy deployments are performed in a combined manner from the physical ramping capability of the unit. This work proposes a pricing rule for frequency regulation reserves considering the usage of units ramping capability for both reserves and intra-dispatch movements in a joint manner, so a co-optimization of reserves and energy considering a complete representation of ramping capability requirements is possible. An illustrative example is presented. © 2020 IEEE.